1970
DOI: 10.1161/01.cir.41.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors in Sudden Cardiac Death in Tecumseh, Michigan

Abstract: In an epidemiologic study of the total population of Tecumseh, Michigan, 98 deaths from coronary heart disease were observed between 1959 and 1965. Forty-five of the fatalities occurred within 1 hour of the onset of symptoms and were classified as sudden. The proportion of sudden deaths among men was nearly twice that among women, and the incidence increased progressively with age in both sexes.Hypertensive heart disease, coronary heart disease, or diabetes mellitus had been detected on prior examination in 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

1970
1970
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(31 citation statements)
references
References 21 publications
(3 reference statements)
5
24
0
2
Order By: Relevance
“…It should be stressed that the application of this correction may possibly result in an unduly concervative result; some authors find this correction altogether unnecessary (9,22). Our observations seem to confirm the data of Chiang et al (2) who found in their Tecumseh study, a higher increase in sudden-death rate among subjects with VPB although in a later article a less definite conclusion was expressed (3). On the other hand, Fisher and Tyroler (6) did not find any significant increase in sudden death in patients with VPB.…”
Section: Discussionsupporting
confidence: 90%
“…It should be stressed that the application of this correction may possibly result in an unduly concervative result; some authors find this correction altogether unnecessary (9,22). Our observations seem to confirm the data of Chiang et al (2) who found in their Tecumseh study, a higher increase in sudden-death rate among subjects with VPB although in a later article a less definite conclusion was expressed (3). On the other hand, Fisher and Tyroler (6) did not find any significant increase in sudden death in patients with VPB.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have implicated over weight as a risk factor for sudden death [1,12,21], some studies have found no causal relationship [5,13].…”
Section: Resultsmentioning
confidence: 99%
“…The clinical significance of asystole for 20 s or more in a young and healthy child is not known. Ventricular fibrillation has been reported in older patients with atrioventricular block and severe bradycardia (22,23). Treatment of severe BHS with a permanent backup pacemaker was reported by Villain et al (24) in a series of 11 patients, in whom prolonged sinus node suppression was documented.…”
Section: Figure 1) a Rhythm Strip From An Event Recorder At The Time mentioning
confidence: 93%